Ontologi Eksistensialisme: Antara Religiusitas dan Non-Religiusitas : (Studi Pemikiran Mulla Shadra dan Jean Paul Sartre) - Lukman Fajariyah (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
The discussion on the field of ontology in philosophical studies always has its own uniqueness. Ontology as a science that discusses the nature of all things stimulates humans to always think and reflect so that in the long span of ontology studies many figures will play a role in that field. Characters who contribute to thinking about nature have their own characteristics. This is represented by figures Mulla Sadra and Jean Paul Sartre. This paper intends to explore the thoughts of Mulla Shadra and Jean Paul Sartre regarding ontology studies by using a comparative approach, where researchers compare or compare the two thoughts of these figures in revealing differences and similarities. The research method used in this paper is a qualitative-descriptive method to clearly describe the object. The findings in this paper are; First, Sadra's existential ontology emphasizes more on the aspect of religiosity in which all the existences in the universe are small parts of God's existence, meaning that all existence depends on its source, namely God. Meanwhile, Secondly, Sartre's existential ontology places more emphasis on human freedom as the main actor in life. According to him, the existence of humans with their freedom is absolute without interference from God (non-religious/atheist), even humans create their own functions and goals.